The emergence of maritime logistics database centre (MLDC): A bibliometrics analysis - Yuthana Autsadee; Jagan Jeevan; Nurul Haqimin Mohd Salleh; Mohamad Rosni Othman; Phansak Iamraksa (Journal of International Maritime Safety, Environmental Affairs, and Shipping)
The MLDC plays a crucial role in providing information on diverse maritime operations activities to enhance efficient and effective management in the maritime sector. This paper explores the essential requirements for establishing a MLDC, examines impacts of database centre (DC), and provides a framework for establishing a MLDC. 873 articles from Scopus were analysed using the VOSviewer and the “Bibliometrix” package to conduct a bibliometric analysis. The findings revealed that the fundamental requirements for MLDC development were classified into seven requirements: cloud computing (CC), environmental control system (ECS), data centre network (DCN), security control system (SCS), database centre design (DCD), power system (PS), and operation and management (OM). The establishment of a DC gives rise to environmental concerns and impacts on the OM performance. An MLDC framework has been proposed and the research highlighted the benefits of MLDC on the maritime industry, such as improved management and operation efficiency, increased operational efficiency, reduced operation costs, and environmental control. This research’s results may help improve managerial efficiency in the maritime sectors. This research provides valuable insights into the requirements for establishing and benefits of a MLDC, contributing to the development of the maritime industry’s DC.